2018
DOI: 10.1016/j.redox.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide releasing molecule-2 attenuates Pseudomonas aeruginosa-induced ROS-dependent ICAM-1 expression in human pulmonary alveolar epithelial cells

Abstract: Pseudomonas aeruginosa (P. aeruginosa) infection in the lung is common in patients with cystic fibrosis (CF). Intercellular adhesion molecule-1 (ICAM-1) is known to play a key role in lung inflammation. Acute inflammation and its timely resolution are important to ensure bacterial clearance and limit tissue damage. Carbon monoxide (CO) has been shown to exert anti-inflammatory effects in various tissues and organ systems. Here, we explored the protective effects and mechanisms of carbon monoxide releasing mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Pseudomonas , a gram-negative bacterium with carbon degradation activity, was the most common pathogen for hospital infection (Hota et al, 2009; Decker and Palmore, 2014; Hung et al, 2016). It can invade the epithelium and induce immune responses through activation of protein kinase C alpha (PKCα), c-Jun N -terminal kinase (JNK), extracellular-regulated protein kinases (ERK1/2), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and/or glutamic acid–leucine–arginine–positive CXC chemokines (Gregson et al, 2013; Chiang-Wen et al, 2018; Curran et al, 2018). Aggregatibacter was associated with aggressive periodontitis (Ando et al, 2010), which can induce inflammatory response through cytolethal distending toxin (CDT), leukotoxin, and lipopolysaccharide (LPS) (Herbert et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas , a gram-negative bacterium with carbon degradation activity, was the most common pathogen for hospital infection (Hota et al, 2009; Decker and Palmore, 2014; Hung et al, 2016). It can invade the epithelium and induce immune responses through activation of protein kinase C alpha (PKCα), c-Jun N -terminal kinase (JNK), extracellular-regulated protein kinases (ERK1/2), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and/or glutamic acid–leucine–arginine–positive CXC chemokines (Gregson et al, 2013; Chiang-Wen et al, 2018; Curran et al, 2018). Aggregatibacter was associated with aggressive periodontitis (Ando et al, 2010), which can induce inflammatory response through cytolethal distending toxin (CDT), leukotoxin, and lipopolysaccharide (LPS) (Herbert et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 36 Moreover, P. aeruginosa infection can activate all three MAPK members, further leading to apoptosis through ROS accumulation. 37 In addition, many lines of evidence confirmed that rapamycin can alter the activity of MAPKs, which further affects cell proliferation, survival and apoptosis. 38 40 We proposed that the autophagy-mediated regulation of MAPK signalling pathway and scavenging ROS should be critical for inhibiting P. aeruginosa- induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the TNF-a and IL-1b exposed human gingival fibroblasts, CORM-3 inhibited adhesion molecules expression by suppressing the NF-kB pathway (Song et al, 2011). Additionally, Cunha and his colleagues demonstrated that the CO donor, dimanganese decacarbonyl, sustained the neutrophils adhesion and migration and ICAM-1 expression depending on soluble guanylate cyclase (sGC) activation (Lee et al, 2018). By the isolating the neutrophils from the PKG-deficient mice, they found the HO/CO/PKG pathway involves in neutrophil migration which might be further explain by the PKG effect on the NF-kB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%